Efficacy of combined hysteroscopy and laparoscopy in the evaluation and management of female infertility at a tertiary care center - Rakholia, Reha; Donthu, Kiranmayi; Sinha, Shweta; Sharma, Sangeeta; Himabindu, Y.; Swapnil; Dubey, Ambika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Infertility, defined by the World Health Organization (WHO) as the inability to achieve pregnancy after one year of unprotected intercourse, is a significant health concern. The study aimed to assess the efficacy of combined hysteroscopy and laparoscopy in diagnosing and managing female infertility, focusing on their impact on pregnancy success rates in a tertiary care setting. Methods: A retrospective observational study was conducted on 170 infertile women aged 20 to 40 years at GSL Medical College from January 2022 to December 2023. Diagnostic and therapeutic hysterolaparoscopy was performed to identify and treat intrauterine and tuboperitoneal abnormalities. Data were analyzed to determine the prevalence of different infertility factors and the effectiveness of these procedures in enhancing fertility outcomes. Results: Of the 170 cases, 129 (75.8%) were diagnosed with primary infertility, and 41 (24.1%) with secondary infertility. The most common abnormalities detected included tubal infertility (19.4%) and endometriosis (14.1%). The overall pregnancy success rate was 31.18%, with significant contributions from ovulation induction, IUI, and in vitro fertilization (IVF). Spontaneous pregnancies were infrequent, highlighting the importance of medical intervention. Conclusions: Combined hysteroscopy and laparoscopy are effective tools for evaluating and managing female infertility. These procedures are particularly valuable in diagnosing and treating conditions like tubal infertility, endometriosis, and uterine anomalies, leading to improved pregnancy outcomes.